POTENSI WAKAF MENJADI LEMBAGA KEUANGAN PUBLIK (Kajian Kritis terhadap Konsep dan Praktik Wakaf dalam Hukum Islam) - Amin Muhtar (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
Waqf is one means to make people more prosperous, it is pointed out that Islam as a religion that always offers mankind to live a more prosperous by way of organizing and managing the waqf. However, several decades after the dissolution of the revelation that explains about waqf, it does not really appear as an offer religion that leads to prosperity. Then Islamic law needs to legitimize waqf back into the practice of more productive endowments and to be a source of public finance.